الذاكرة و التاريخ في الرواية بين "التطهير" لصوفي أوكسانين و "زرايب العبيد" لنجوى بن شتوان دراسة تحليلية مقارنة (Faculty of Education Scientific Journal, 2026)
The dialectical relationship between individual memory and official history constitutes a problematic field, central to contemporary literary narratives, especially those that deal with historical periods that witnessed deliberate obliteration and concealment of counter-narrativesThis study aims to shed light on this critical dialogue by examining the representations of this relationship in two narrative models, belonging to two different cultural and geographical contexts: the novel "Puhdistus" by the Finnish-Estonian writer Sofi Oksanen, and the novel "Slave Pens" by the Libyan writer Najwa Bin Shatwan. This comparison is based on the basic premise that both texts, despite their divergent historical references—the Soviet occupation of Estonia on the one hand, and the history of slavery in Libya on the other—intersect in that they constitute a literary project that uses narrative as a tool of resistance against forgetting and a reconstruction of a counternarrative to the dominant official history. The study will analyze the similarities and differences between the two novels in how they employ personal memory as a living archive that refutes the narrative of dominant power and as a struggle to reclaim identity and humanity.
Keywords: Memory; Novel; Slave Pens; Purification; Comparison